Dokąd zmierza lewica. Aktualne polskie partie lewicowe w zestawieniu z klasycznymi postulatami - Bajon, Mateusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article analyzes contemporary Polish political parties declaring leftist values, focusing on three classic pillars of leftist ideology: popular will, equality and solidarity. The analysis includes six parties: the Polish Initiative, the Greens, the New Left, the Polish Socialist Party (PPS), the Labor Union and the Left Together. The study is based on a review of the parties` statutes, their program declarations and actions taken in the public space. In the context of contemporary politics, the author notes that left-wing parties in Poland often function within broader coalitions, forcing ideological compromises.
Keywords: lewica; partie polityczne; wola powszechna; równość; solidarność; wybory parlamentarne; Polska; left; popular will; equality; solidarity; parliamentary elections; Poland